Productions of a beverage orange juice and sweet whey mixture - سلطانة علي; حرفوش محسن; الضرف ربى (Latakia University Journal -Biological Sciences Series, 2014)
Attempts were made to develop a soft beverage of orange juice and sweet whey mixture using different concentrations of pectin. The beverage prepared composition was 50% sweet whey cheese, 50% orange juice and three different concentrations of pectin (0.5,1,1.5%) and pasteurized at 80Cº for 15 minutes and it evaluated of chemical characteristics( viscosity, sedimentation and degree of separation) at 7±2 Cº for 20 days . The results showed an increasing of TSS (Total soluble solids), acidity, viscosity, sedimentation and the degree of separation, and a decreasing of pH values during applicated conditions . and also showed that the 1% pectin beverage had the best storage stability. إنتاج المشروبات من مصل الجبن وعصير البرتقال تم إجراء العديد من المحاولات لتطوير المشروبات المصنعة من مصل الجبن الحلو وعصير البرتقال وبإضافة تراكيز مختلفة من البكتين. تم تحضير مشروبات مكونة من 50% مصل الجبن الحلو و50% عصير البرتقال وثلاث تراكيز (0.5، 1، 1.5%). بستر الشراب المحضر على الدرجة 80 مْ لمدة 15 دقيقة. كما تم تقييم الخصائص الفيز وكيماوية للشراب (اللزوجة، الراسب، مقدار الانفصال) وذلك خلال فترة التخزين على الدرجة 7 ± 2 مْ لمدة 20 يوم. أظهرت النتائج ارتفاع في قيمة كل من المواد الصلبة الذائبة والحموضة واللزوجة والراسب ومقدار الانفصال، وانخفاض في قيمة الأس الهيدروجيني، كما أظهرت النتائج أن النسبة 1% من البكتين المضافة كانت الأفضل لتحقيق الثباتية خلال فترة التخزين.